Incidence and consequences of inbreeding in Karan Fries cattle - SAHA, SUJIT; JOSHI, B K; SINGH, AVTAR (The Indian Journal of Animal Sciences, 2011)
The study was carried out on 3051 Karan Fries cows maintained at NDRI, Karnal during 1965 to 2000. Out of total, only 9.24% animals were found to be inbred with an average inbreeding coefficient of 3.65 %. Among the inbreds, majority of the animals (76.5 %) were lowly inbred with inbreeding coefficient below 6 %. No inbreds were found in the first generation from paternal as well as maternal side. Incidence of inbreeding followed an increasing trend over the generations, whereas, level of inbreeding reduced over the generations. Detrimental effect of inbreeding on various performance traits was observed. Animals with inbreeding coefficient more than 12% were poorer with respect to various growth, first lactation production and reproduction traits and herd life. However, the effect of inbreeding was found significant only for weight at one year (WOY) and herdlife (HL) in Karan Fries females, whereas, for other traits the effect was statistically nonsignificant. Regression of various performance traits on inbreeding indicated the deleterious effect of inbreeding on the respective traits. Regression coefficients were nonsignificant for all the traits. Depressing effect of inbreeding may be due to increase in the homozygosity with respect to recessive alleles.